“The death of sympathy”: coal mining, workplace hazards, and the politics of risk in Britain, ca. 1970-1990 - Arnold, Jörg (GESIS, 2016)
"Das Ende des Mitleids: Steinkohlebergbau, Gefahren am Arbeitsplatz und Risikopolitik in Großbritannien, ca. 1970-1990". This article employs the concept of risk as a lens through which to explore discursive constructions of the nature of coal mining and coal miners in the UK in the 1970s and 1980s. Drawing on a diverse primary source base, ranging from songs and poetry to parliamentary debates and government files, it contextualises and refines labour historian Dick Geary’s observation about the “death of sympathy” for the miners in the coal strike of 1984/85. It argues that over the course of the period, coal miners turned from an object of risk into its subject; they were transformed, in political discourse, from heroes and victims into enemies of the state and society. Although the notion that coal miners were a “special case” on account of the hazardous working conditions in which they laboured, continued to resonate in popular culture throughout the 1970s and 1980s, the political bargaining power of the “blood on the coal” argument became progressively eroded after its successful application in the strikes of 1972 and 1974. By the time of the strike of 1984/85, Conservative opponents of the miners’ cause had turned the argument on its head: The very hazardous working conditions were taken as proof of an obstinate refusal of the industry to go with the times. The real danger, they argued, were not health hazards, but the miners themselves.